Qualified care in prenatal as a prevention of obstetric violence: Integrative review (Research, Society and Development, 2021)
Obstetric violence comprises the aggressions suffered by pregnant women during prenatal care, childbirth or puerperium practiced by health professionals. This study aimed to analyze how the health care offered by health professionals during prenatal care can contribute to the prevention of obstetric violence. This is an integrative literature review, collected in the Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) databases and the Scientific Electronic Library Online (SciELO) journal portal ) indexed in the Virtual Health Library, through the descriptors “obstetric violence”, “health care” and “prenatal care”, with the help of the Boolean operator AND. Eleven publications were selected that dealt with the theme, in which women's lack of knowledge about obstetric violence was highlighted, as well as the professionals' lack of preparation, due to gaps during graduation. Therefore, it emphasizes the need for professionals to offer quality care, in a humanized and individualized manner, from prenatal care to the puerperium, with clarification of doubts and legal rights that are guaranteed by law. As well as the development of training for the management and identification of obstetric violence for professionals and educational activities for pregnant women, companions, among others.